2018
DOI: 10.1007/s00289-018-2455-2
|View full text |Cite
|
Sign up to set email alerts
|

Conformational modeling of the system pollutant/three-dimensional poly (2-hydroxyethyl methacrylate) (PHEMA) in aqueous medium: a new approach

Abstract: The polluted water, mixture of chemicals and dyes, discharged by various textile and paper industries, is a serious problem for the environment, peculiarly the water. Dyes are stable to light, heat and oxidizing agents and are usually biologically non-degradable, which makes them complicated environmental pollutants. To examine the removal of dye from water, a three-dimensional poly (2-hydroxyethyl methacrylate) (PHEMA) and eosin Y were used, respectively, as a dye retention support and pollutant. The study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The distance between atoms has, thus, an important effect on the interactions of the system. It was found that interactions can be classified as strong and medium for a distance interval of [2.5, 3.1] Å and [3.1, 3.55] Å, respectively, whereas distances between selected atoms greater than 3.55Å correspond to weak or non-existing interactions [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between atoms has, thus, an important effect on the interactions of the system. It was found that interactions can be classified as strong and medium for a distance interval of [2.5, 3.1] Å and [3.1, 3.55] Å, respectively, whereas distances between selected atoms greater than 3.55Å correspond to weak or non-existing interactions [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper [ 41 ], the interaction between a polymer based on HEMA monomer and Eosin Y (EY) as a pollutant was discussed. It was found that the theoretical prediction correlates well with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The polyacrylamide (AM)-co-acrylic acid (AA) copolymer was effectively used to eliminate Safranine-O SO and Magenta M dyes [21]. In a previous study [22,23], a crosslinked poly(AM-co-AA)/1,6-hexanediol diacrylate (HDDA) hydrogel was applied to remove Rose Bengal (RB), MB, and Eosin Y (EY), resulting in retention percentages of 98%, 50%, and 58%, respectively. The method employed is effective and promising in eliminating these dyes.…”
Section: Introductionmentioning
confidence: 99%
“…This simulation method is largely used in the field of biology to explain the interaction between ligands and enzymes [ 34 ]. In a previous research article [ 35 ], the crosslinked PHEMA-co-HDDA was used for the removal of eosin Y and green malachite pollutants. According to the obtained results, this network showed a low absorption capacity for eosin Y and a high absorption capacity for green malachite.…”
Section: Introductionmentioning
confidence: 99%